Adaptation and validation of the vocabulary learning motivation questionnaire for Chinese learners: A construct validation approach. (August 2022) - Li, Jiajing; King, Ronnel B.; Wang, Chuang
Abstract: English as a foreign language (EFL) learners in China view learning vocabulary as one of their biggest challenges. Despite the importance of vocabulary learning for mastering English, no existing survey specifically measures Chinese students' vocabulary learning motivation. This study aimed to cross-culturally adapt the Vocabulary Learning Motivation Questionnaire (VLMQ; Tanaka, 2017) and validated it in a Chinese context. Both within- and between-network approaches were used. Results indicated the applicability of this new version of the scale (i.e., VLMQ-Chinese) in measuring the vocabulary learning motivation of Chinese high school students. Results of the within-network analyses supported the four-factor model of the scale which includes intrinsic, identified, introjected, and external motivation. Measurement invariance across gender was also supported. The between-network analyses indicated that different types of motivation were associated with students' vocabulary proficiency, self-efficacy, and self-regulating capacity in vocabulary learning. Among the different types of motivation, intrinsic motivation and identified motivation were more strongly associated with adaptive learning-related outcomes. Theoretically, this study extends the past vocabulary learning literature by focusing specifically on Chinese EFL learners' vocabulary learning motivation. Practically, this study provides researchers and educators with a tool to measure students' motivation in vocabulary learning.